CHARACTER ANALYSIS: ETHICS AND CARE OF STUDENTS ON CLEANLINESS OF MUSHOLLA FLOORS AND SCHOOL TOILETS - Rejeki, Tutik Sri; Subchan, Wachju (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
This research aims to describe the ethics of cleanliness care of prayer room floor and school toilet at State Junior High School 1 Bangsalsari, Jember in the 2019-2020 Academic Year. The research is a qualitative descriptive with the number of respondents 102 students. The data collection technique using questionnaires about the mosque's floor and toilet hygiene schools is distributed via Google form. The average percentage of hygiene care characters is calculated and then compared to the awareness level criteria. The results of the study were 75% of students choosing to solve their own problems encountered; 22% ordered or asked someone else's help to solve it; 21.25% let it go. The data shows that students of Junior High School 1 Bangsalsari have good environmental concerns. Factors affecting the toilet of urine students are known from the urine ethic's questionnaire of students in the school toilet as much as 8% of male students choose to sometimes flush their urine. This habit can cause urine odor. Efforts that can be made are the School Principal and a Teacher giving advice and an exemplary way of maintaining the cleanliness of the mosque and school toilet.